PENGARUH MEDIA BIG BOOK TERHADAP KETERAMPILAN MENULIS PUISI SISWA SEKOLAH DASAR - Sigit Vebrianto Susilo; Devi Afriyuni Yonanda; Rieta Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the lack of students in poetry writing skills. This study aims to determine the effect ofmedia Big Book on poetry writing skills as well as differences in poetry writing skills between groups of students who take thelearning media Big Book and groups of students who take conventional learning. This research is a quasi-experimental design with Nonequivalent Control Group Design. The sample in this study were students in class IVA with a total of 20 students and students in class IVB with a total of 20 students, students of SD Negeri Kalapadua I, Lemahsugih Sub-district, Majalengka Regency, who were determined by simple random sampling technique by lottery. Data collection techniques through written tests using the Process Worksheet (LKP), observation sheets and documentation. Analysis of the data used is qualitative data and quantitative data. Qualitative data were obtained from teacher and student observation sheets and quantitative data were analyzed through statistical description tests, normality tests and Mann-Whitney tests or U tests. Based on the results of data analysis, it showed that: 1) there were significant differences in the initial ability of poetry writing skills between experimental classes and control class. But it can be seen from the results of the average value that the experimental class data of 34.00 lower than the average value of the overall control class of 42.00 can be said that the initial ability of the control class is better than the experimental class before the treatment is given. 2) there is a significant difference in poetry writing skills between classes using big book media and those applying conventional learning that is Sig. (2-tailed) 0,000 <0.05. Abstrak Penelitian ini dilatarbelakangi oleh rendahnya siswa dalam keterampilan menulis puisi. Penelitian ini bertujuan mengetahui pengaruh media Big Book terhadap keterampilan menulis puisi serta perbedaan keterampilan menulis puisi antara kelompok siswa yang mengikuti media pembelajaran Big Book dengan kelompok siswa yang mengikuti pembelajaran konvensional. Penelitian ini merupakan kuasi eksperimen dengan desain Nonequivalent Control Group Desain. Sampel dalam penelitian ini yaitu siswa kelas IVA dengan jumlah 20 siswa dan siswa kelas IVB dengan jumlah siswa 20, siswa SD Negeri Kalapadua I Kecamatan Lemahsugih Kabupaten Majalengka yang ditentukan dengan teknik simple random sampling dengan cara undian. Teknik pengumpulan data melalui tes tertulis menggunakan Lembar Kerja Proses (LKP), lembar observasi dan dokumentasi. Analisis data yang digunakan yaitu data kualitatif dan data kuantitatif. Data kualitatif diperoleh dari lembar observasi guru dan siswa dan data kuantitaif dianalisis melalui uji deskripsi statistik, uji normalitas dan uji Mann-Whitney atau uji U. Berdasarkan hasil analisis data menunjukkan bahwa : 1) terdapat perbedaan yang signifikan kemampuan awal keterampilan menulis puisi antara kelas eksperimen dan kelas kontrol. Tetapi dapat dilihat dari hasil nilai rata-rata bahwa data kelas eksperimen sebesar 34,00 lebih rendah dibandingkan dengan nilai rata – rata kelas kontrol secara keseluruhan sebesar 42,00 dapat dikatakan bahwa kemampuan awal kelas kontrol lebih baik dibandingkan dengan kelas eksperimen sebelum diberikannya perlakuan. 2) terdapat perbedaan yang signifikan terhadap keterampilan menulis puisi antara kelas yang menggunakan media big book dengan yang menerapkan pembelajaran konvensional yaitu nilai Sig. (2-tailed) 0,000 <0,05. Kata Kunci: Big Book, Keterampilan Menulis Puisi